PENGARUH LINGKUNGAN KERJA FISIK DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MAKAN IKAN INDONESIA ‘NGIKAN YUK!’ PONDOK PINANG JAKARTA SELATAN - Tika Istiqomah; Shela Indah Savitri (Jurnal Menara, 2025)
This study aims to see the influence of the physical work environment and workload on employee performance at PT. Makan Ikan Indonesia 'Ngikan Yuk!' partially and simultaneously. The respondents used were 60 employees. This study used a questionnaire as a data collection tool. The data analysis method used was simple and multiple regression analysis. The results of this study indicate that the physical work environment has a positive and significant effect on employee performance. This is indicated by the calculated t value of 7.702 (positive sign) and the significance level of p value is 0.002 <0.050. In addition, the workload has a positive and significant effect on employee performance with a calculated t value of 5.234 (positive sign) and the significance level of p value is 0.000 <0.050. Simultaneously, the physical work environment and workload have a positive and significant effect on employee performance. This is confirmed by the results of the F test which shows a significance value of 0.000 <0.050. These findings indicate that the level of employee performance at PT. Makan Ikan Indonesia 'Ngikan Yuk!' Influenced by the physical work environment and workload.